International Portfolio and Currency Risk Management - Pham, Huynh Duc (2025)
This research focuses on the creation and management of international diversified investment portfolios, especially in relation to currency risk. It highlights the enduring problem of systemic and currency risks associated with global investments. The study analyzes the practical and theoretical aspects of hedging tools like forwards and options. An empirical analysis simulates a five-year investment plan for an investor, measuring returns, volatility, and Sharpe ratios for hedged and unhedged portfolios against benchmarks. The findings reveal that robust currency hedging fortifies risk-adjusted performance, which enhances portfolio outcomes and minimizes foreign exchange risk.